Caring for carers: exploring the benefits of group support for carers of people with pulmonary fibrosis. (2nd January 2021) - Dean, Antonia; Miller, Barbara; Hewitt, Claire; Cook, Manisha; Nicell, Claire; Spicer, Karenann
Abstract : Limited evidence suggests carers of people with pulmonary fibrosis (PF) have a variety of information and support needs. This pilot focus group discussion, carried out in 2019, aimed to explore the needs of carers of people with pulmonary fibrosis and evaluate the impact of a UK hospice PF carers' support group. Analysis revealed: (1) loneliness and connection, (2) negotiating with and motivating their loved-ones, and (3) the importance of the best environment for support as key themes. Participants reported a need for both practical and emotional support with the carers' own health sometimes neglected. This evaluation concluded that peer support specifically with other PF carers was hugely valuable to the participants, as was the hospice environment itself. It is recommended that PF-specific carer support is considered when designing services for people with pulmonary fibrosis.